Stability and Bifurcation Analysis for a Predator-Prey Model with Crowley-Martin Functional Response (Journal of Nonlinear Modeling and Analysis, 2025)
This paper mainly focuses on the Gauze-type predator-prey modelwith Crowley-Martin functional response. The local stability of the equilibriais investigated by analyzing the characteristic equation and using the Routh-Hurwitz criterion. Besides, dynamic behavior has been studied by using thecenter manifold theorem and normal form theory. Finally, several numericalsimulations not only verify the theoretical results of Hopf bifurcation but alsodisplay more interesting dynamical properties of the model.